Active Herpes Virus Infection in Young Children - N. Yu. Egorova; O. V. Molochkova; L. N. Guseva; N. L. Waltz; K. P. Chusov (Детские инфекции (Москва))
Under observation were 122 young children (up to 3 years of age), who were identified markers of active forms of herpes virus infections. Markers were studied by PCR in blood, smear from tonsils, saliva, cerebrospinal fluid, urine with determination DNA of HSV 1—2 type, EBV, CMV, HHV-6 type, antigens were determined by indirect immunofluorescence in blood lymphocytes, by ELISA in serum — antibodies of the classes IgM and IgG. Herpesvirus infection occurs at an early age and contributes to the formation of various infectious and somatic pathology. In children from birth to 1 year of life, CMV infection in the form of a mono-infection with symptoms of CNS damage, generalized forms, neutropenia is more common (79% of cases). In children aged 1 to 2 years, in 76% of cases, HHV-6 infection is detected, more often in mixed variants. Patients of this group are observed with a long subfebrile condition, neutropenia, infectious mononucleosis. In the third year of life, there is an increase in infection of children with EBV, with approximately the same frequency of EBV and HHV-6, most often in mixed forms, the clinical manifestations of which is a typical symptom complex of infectious mononucleosis. At this age, the active persistence of herpes viruses contributes to the formation of a group of frequently ill children. Thus, when examining young children with various pathologies, it is necessary to diagnose herpes virus infection using modern methods to detect its active forms for the timely administration of etiotropic therapy.